Determinantes macroeconômicos do spread bancário no Brasil: teoria e evidência recente - Oreiro, José Luís da Costa (2006)
Due to the successful implementation of the price stabilization programme (Real Plan), the greater international financial integration and, more recently, the adoption of a floating exchange rate regime, it was expected in Brazil a sharp decline of the banking interest spreads converging to the international levels. However, such a reduction did not materialized. Indeed, one of the main factors to why the ratio total credit over GDP is still low in Brazil is the very high loan interest rates. The paper aims to at analyze the macroeconomic determinants of banking spread in Brazil. For this purpose, we make use of a multiple regression analysis with the objective to find what macroeconomic variables are determining, directly or indirectly, the banking spread in the period 1994-2003. The results show that the high volatility of the short-term interest rate (Selic) and its level are the main macroeconomic determinants of the banking spread in Brazil.